1997
DOI: 10.1183/09031936.97.10122847
|View full text |Cite
|
Sign up to set email alerts
|

Influence of noninvasive positive pressure ventilation on inspiratory muscle activity in obese subjects

Abstract: Noninvasive positive pressure ventilation (NPPV) can improve ventilation in obese subjects during the postoperative period after abdominal surgery. Compared to nasal continuous positive airway pressure (nCPAP), NPPV was superior in correcting blood gas abnormalities both during the night-time and during the daytime in a subgroup of patients with the obesity hypoventilation syndrome (OHS). However, as it is unknown, if and to what extent NPPV can unload the respiratory muscles in the face of the increased imped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 28 publications
4
47
0
7
Order By: Relevance
“…Studies have suggested that both CPAP and bilevel noninvasive ventilation (NIV) are useful modes of treatment for OHS. 23,24 NIV maintains upper airway patency, reduces respiratory muscle loading and improves gas exchange leading to an improvement in daytime symptoms and QoL.…”
Section: Respiratory Management Of Obesity-related Respiratory Failurementioning
confidence: 99%
“…Studies have suggested that both CPAP and bilevel noninvasive ventilation (NIV) are useful modes of treatment for OHS. 23,24 NIV maintains upper airway patency, reduces respiratory muscle loading and improves gas exchange leading to an improvement in daytime symptoms and QoL.…”
Section: Respiratory Management Of Obesity-related Respiratory Failurementioning
confidence: 99%
“…When analyzing the effects of NIV on the activity of inspiratory muscles in obese patients, Pankow et al 34 found a 46% reduction in diaphragm's activity with the use of the BiPAP. The authors concluded that the assisted NIV can cause partial inactivation of the respiratory muscles in patients with severe obesity 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the bi-level pressure support ventilation may unload the respiratory muscles in patients with class III obesity was demonstrated by PANKOW et al [71], who studied 18 patients with simple obesity, OHS or OSAHS, measured trans-diaphragmatic pressure and pressure-time index, and, with low inspiratory positive airway pressure values up to 1.2 kPa, found a 46% reduction in diaphragmatic activity.…”
Section: Ventilatory Support In Patients With Ohs: Cpap Bi-level Prementioning
confidence: 99%